2021
DOI: 10.5430/mos.v7n1p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leadership Behaviors on Organization Agility: A Quantitative Study of 126 U.S.-Based Business Units

Abstract: Researchers have theorized that the behaviors of organization leaders impact organization agility, which is defined as the ability of an organization to swiftly and successfully change in order to achieve long-term success. The purpose of this study was to determine if leadership behaviors as measured by the MLQ-5X predict organization agility as measured by the Agility Survey (short-form). The research sample included 126 U.S.-based business units within 47 organizations with greater than 1,000 employees. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Leaders are able to invite many people to see other points of view that can be used as ideas to achieve targets. Leaders who have agility need two things, namely dynamic abilities, namely the ability to move quickly, responsiveness or adaptability; the second is stability, which includes durability, reliability, and efficiency (Gagel, 2021;Kustyadji, Gatot, 2021;Nururly, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Leaders are able to invite many people to see other points of view that can be used as ideas to achieve targets. Leaders who have agility need two things, namely dynamic abilities, namely the ability to move quickly, responsiveness or adaptability; the second is stability, which includes durability, reliability, and efficiency (Gagel, 2021;Kustyadji, Gatot, 2021;Nururly, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The research findings demonstrated that the perceptions of business people regarding organizational agility of their organizations and their perceptions about the competency, flexibility and responsiveness sub-dimensions that constitute the organizational agility scale were at high level, and their perceptions about the quickness sub-dimension were at very high level. Agility, which is defined as the ability to succeed in an ever-changing and unpredictable environment (Goldman, Nagel, & Preiss, 1995), is an organization's ability to dynamically respond to complex, turbulent and ambiguous and demanding internal and external factors (Young, 2013). Therefore, business people's high level of agility perceptions about their organizations may be considered as a positive situation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, considering the fact that educated, professional and experienced managers will be at the top management of successful organizations and regarding the issues highlighted in the previous paragraph, it can be evaluated as an expected situation that business people may have higher levels of organizational agility perception for successful organizations. As a matter of fact, as stated by Goldman et al (1995), one of the most basic features of agile organizations is that they are highly qualified in terms of knowledge and skills, have detailed information about the organization and are compatible and flexible in order to meet customer demands that differ with organizational changes.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Glenn, M. (2009), Kasali R, (2014), Alhadid, A. (2016), Hamidianpour, at.al, (2016), Gagel, (2018), and Anna T. Walter, (2019). This era is very familiar with the term VUCA or volatility, uncertainty, complexity and ambiguity, which is an era full of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…DuBrin (2015) also said that a common trait of leaders is their ability to inspire and stimulate others to achieve valuable goals. Leadership can be defined as trust and support among people to achieve organizational goals Gagel, (2018).…”
Section: Introductionmentioning
confidence: 99%